Unsung heroines of the Hebrew bible : a contextual theological reading from the perspective of woman wisdom - Olojede, Funlola Oluseyi (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2011.